Application of an objective method of assessing intention tremor - a further study on the use of weights to reduce intention tremor. Issue 3 (March 1975) - Morgan, M H; Hewer, R L; Cooper, R
Abstract : Thirty-one patients with intention tremor due to a variety of causes were subjected to measurements of their intention tremor. The effect of varying amounts of lead weights on the amount of limb tremor recorded was noted. It is concluded that simple methods of treatment may be of benefit, and that an objective method of measuring intention tremor overcomes many of the difficulties of a clinical trial of this type. The method described yields quantifiable data which can be subjected to statistical analysis to help overcome the problem of variability. Bias in the results due to practice or fatigue effects has proved negligible. An optimum amount of lead, which was usually between 600 and 840 g, has been noted.